Makna Nilai dan Fungsi Kebudayaan Islam Jawa dalam Kesenian Selawat Gembrungan di Dukuh Purwosari, Desa Gelanglor, Kabupaten Ponorogo: The Meaning of the Values and Functions of Javanese Islamic Culture in the Selawat Gembrungan Art in Purwosari Hamlet, Gelanglor Village, Ponorogo Regency - Restu, Adhie Handika; Sa'adillah, Aldho Efbinawan (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This study aims to reveal the meaning behind Javanese Islamic culture in the art of Selawat Gembrungan found in Dukuh Purwosari, Gelanglor Village, Sukorejo District, Ponorogo Regency. This study uses an ethnographic approach to describe in depth the condition of the art and its relationship to Islamic teachings. In collecting data, this study utilized interviews and relevant literature studies. The data obtained were analyzed through verification and interpretation stages to describe the values ​​and functions of the art of Selawat Gembrungan in Dukuh Purwosari. The study results show that, first, Javanese Islamic values ​​are reflected in the musical collaboration between elements of Islamic and Javanese art found in this art. The poetry of Selawat Gembrungan is also adapted from Arabic text into Javanese Pegon Malay text. Second, this art provides benefits to society in the form of educational functions, social functions, and religious functions.